Characteristics of the soils of Ladakh region of Jammu and Kashmir - GUPTA, R. D.; ARORA, SANJAY (Journal of Soil and Water Conservation, 2020)
The cold arid region of Ladakh has high variability in soil characteristics. Soils of the region are quite distinct from those of other zones due to differences in climate, topography, vegetation and rocks. The paper details soil characteristics along with physiography, geology and climate of the region. Soils not only vary in physico-chemical properties but also in genesis and classification as well as microbiological properties. Such properties have been studied in typical soil profiles. By and large, the soils are shallow to very shallow in depth. They vary widely in colour, texture, structure and permeability depending upon topography and vegetation. Under the predominant influence of physical weathering, these soils usually consist of coarse materials and are often called Skeletal soils with admixtures of distinguished rock fragments, colluvial materials and screes. Most of the morphological characteristics like colour, texture and permeability seem to be inherited from the so formed regolith due to very slow rate of soil forming process. Calcareous nature of parental rocks in the form of limestone, dolomitic limestone and shale, is responsible for the genesis of soils having free CaCO3. Based on the surface and subsurface diagnostic horizons, morphological, physico-chemical and chemical characteristics of the soils, they have been classified into three main orders viz. Entisols, Inceptisols, Mollisols with occasional presence of Alfisols.